Three new Solomon’s Seals (Polygonatum: Asparagaceae) from the Eastern Himalaya - Floden, Aaron Jennings (Phytotaxa, 2015)
Three new Polygonatum (Asparagaceae) are described and illustrated from the Eastern Himalaya. These species, Polygonatum autumnale, P. angelicum, and P. luteoverrucosum, have opposite leaves and are evergreen. The foremost is the first autumn-flowering species in the genus and is known from a single locality in Arunachal Pradesh, India. Polygonatum angelicum and P. luteoverrucosum are the first species in the genus to be reported with distinctly verrucose perigone surfaces. These two are sympatric in Arunachal Pradesh, India, and Xizang, China, but occur at different elevations. Their relationships to other opposite-leaved species are discussed and a key is provided to these and related species.